UMPSA Decorated Car with a technology concept is the focus of 2024 Pahang Peoples Carnival Night - Mimi Rabita, Abd Wahit (UMPSA, 2024)
KUANTAN, 2 February 2024 - The decorated car of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) was celebrated and became the focus when it came up with the concept of technology in conjunction with the Pahang People’s Carnival Night 2024.